2012
DOI: 10.1002/eji.201242806
|View full text |Cite
|
Sign up to set email alerts
|

Host defense against DNA virus infection in shrimp is mediated by the siRNA pathway

Abstract: The RNA interference (RNAi) system of eukaryotes using siRNAs has been documented as an immune response against invasion by RNA viruses. However, whether the siRNA pathway can be triggered by the infection with DNA viruses in animals remains to be investigated. In the present study, we show that Marsupenaeus japonicus shrimp can generate an antiviral siRNA (vp28-siRNA) in response to infection by a double-stranded DNA virus, white spot syndrome virus (WSSV). After challenging with WSSV, vp28-siRNA is detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
2
35
0
1
Order By: Relevance
“…Recently, it was revealed that hosts can use virus-derived siRNA or cellular miRNA to restrict viral propagation (18,(21)(22)(23)(24). In turn, a number of viruses, in particular DNA viruses, seem to have evolved mechanisms to express their own miRNAs and employ miRNA-mediated regulations to counter host antiviral responses (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that hosts can use virus-derived siRNA or cellular miRNA to restrict viral propagation (18,(21)(22)(23)(24). In turn, a number of viruses, in particular DNA viruses, seem to have evolved mechanisms to express their own miRNAs and employ miRNA-mediated regulations to counter host antiviral responses (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that LvDcr2 and LvAgo2 are directly involved in the RNAi response 17, 18 , while LvSid-1 is a putative dsRNA transport molecule potentially involved in uptake and communication of a dsRNA signal between cells 19 . We show how dsRNA induces upregulation of these genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As for Drosophila 1416 , P. vannamei has been found to encode two variants of Dicer and Argonaute, and among these LvDcr2 and LvAgo2 are employed by the siRNA pathway 1719 . Although Dcr1 and Ago1 are normally associated with the miRNA pathway in Drosophila 14, 20 , a possible involvement in the antiviral response has been shown for homologue genes in white leg shrimp 2123 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, synthesized dsRNA confers protective effects against YHV infection in P. monodon, and the effect lasts for five days (Yodmuang et al, 2006). Continuous injections of vp28-siRNA at different times post-challenge completely eliminate WSSV in M. japonicus shrimp Huang and Zhang, 2013). When administered prophylactically to shrimp before a viral challenge, in vitro-transcribed long dsRNA or siRNA corresponding to viral genes vp28, vp281, and vp19 results in a high survival rate (Kim et al, 2007;Xu et al, 2007).…”
Section: Sirna-related Antiviral Response In Crustaceansmentioning
confidence: 99%